Liveness in modern music : musicians, technology, and the perception of performance - Sanden, Paul. (Routledge research in music ;, 2013)
This study investigates the idea and practice of liveness in modern music. Understanding what makes music live in an ever-changing musical and technological terrain is one of the more complex and timely challenges facing scholars of current music, where liveness is typically understood to represent performance and to stand in opposition to recording, amplification, and other methods of electronically mediating music. The book argues that liveness itself emerges from dynamic tensions inherent in mediated musical contexts--tensions between music as an acoustic human utterance, and musical sound as something produced or altered by machines. Sanden analyzes liveness in mediatized music (music for which electronic mediation plays an intrinsically defining role), exploring the role this concept plays in defining musical meaning. In discussions of music from both popular and classical traditions, Sanden demonstrates how liveness is performed by acts of human expression in productive tension with the electronic machines involved in making this music, whether on stage or on recording. Liveness is not a fixed ontological state that exists in the absence of electronic mediation, but rather a dynamically performed assertion of human presence within a technological network of communication. This book provides new insights into how the ideas of performance and liveness continue to permeate the perception and reception of even highly mediatized music within a society so deeply invested, on every level, with the use of electronic technologies.